Not by faith alone social services, social justice, and faith-based organizations in the United States - Adkins, Julie, 1960-; Occhipinti, Laurie A., 1968-; Hefferan, Tara, 1972- (Lanham, Md. : Lexington Books, 2010)
"This edited collection provides an in-depth ethnographic study of faith-based development organizations in the United States, shining a critical light onto these organizations and their role by exploring the varied ways that faith-based organizations attempt to mend the fissures and mitigate the effects of neoliberal capitalism, poverty, and the social service sector on the poor and powerless"--P. [4] of cover.
Social services, social justice, and faith-based organizations in the United States : an introduction / Julie Adkins, Laurie Occhipinti, and Tara Hefferan -- A theology of presence : faith partnerships with U.S. public schools / Leah Mundell -- On the border : faith-based initiatives and pentecostal praxis in Brownsville, Texas / Ethan P. Sharp -- Faith-based development and community renaissance : tradition and transformation in South Memphis / Katherine Lambert-Pennington and Julie Pfromm -- Bricks without straw : faith-based responses to homelessness in the hostile city / Julie Adkins -- Muslims, medicine, and mercy : free clinics in southern California / Lance D. Laird and Wendy Cadge -- Culture, history, and discourse at Tree of Life, a faith-based relief agency in Mission, South Dakota / Janet G. Brashler -- What's Islam got to do with it? American pluralism, ethnographic sensibilities, and faith-based refugee resettlement in Hartford, Connecticut / Janet Bauer and Andrea Chivakos -- Translating religious traditions into service : lessons from the Faith and Organizations Project / Jo Anne Schneider, Laura Polk, and Isaac Morrison -- Religious organizational identity and environmental demands / Scott T. Fitzgerald -- "Bio-pistis" : conversion of heroin addicts in prisons, on medicine, and with God / Timoteo Rodriguez -- Straight from the devil : contours of "the public" in American public health / William Garriott.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social service -- United States; Social justice -- United States; Religious institutions -- United States; Faith-based human services -- United States; SOCIAL SCIENCE / Philanthropy & Charity; Electronic books